Tarkovsky’s Influence on American Culture (“Weird” and “Eerie” Cosmos of Christopher Nolan, Jonathan Nolan, and Andrei Tarkovsky) - Lyubov D. Bugaeva (Литература двух Америк)
In the United States, attention to Andrei Tarkovsky’s work has been extensive: Tarkovsky is an important reference point for both filmmakers and film theorists. Paul Schrader refers to him as a transcendental filmmaker and, moreover, introduces the notion of “Tarkovsky’s ring”, with which he correlates transcendental slow cinema that is experimental in nature. The forms and ways that American directors refer to Tarkovsky, who regard him as a cultural resource, are diverse: from overlaps at the level of visual images and frame composition to correspondences at the conceptual level and coincidence of worldviews. The author compares Christopher Nolan’s film Interstellar (2014) and Jonathan Nolan’s screenplay of the same name with Andrei Tarkovsky’s films Solaris (1972) and Stalker (1979). The author suggests that the connection between Nolan’s cinematography and Tarkovsky’s work is evident in the encounters with the weird, characterized by “the presence of that which does not correspond (does not belong) to reality”, and the eerie, characterized by a “failure of absence” or, on the contrary, a “failure of presence”, and appearing in spaces that are partially or completely devoid of human beings. The directors’ recourse to the weird and the eerie as narrative modes, as well as the solastalgic and nostalgic experiences of the character associated with the “home” from which his space journey begins, allow us to speak of the creation of a special “atmosphere”, in the terminology of Gernot Böhme. The absence of image of aliens and the theme of contact with aliens in Nolan’s and Tarkovsky’s “space odysseys”, and the foregrounding of an intimate story about human feelings and relationships, in contrast with the cosmic scale of the universe, contributes to the transfer of the narrative to a metaphysical level. Nolan, like Tarkovsky, departs largely from the conventions of the science fiction genre. A close analysis of the script and film “Interstellar” leads the author to conclude that Jonathan Nolan and Christopher Nolan’s approach to the theme of outer space, bringing them closer to the “Tarkovsky ring”, blurs the boundaries of the science fiction genre.